Gastrointestinal hemorrhage as an uncommon form of presentation of primary intestinal amyloidosis: case report - Fernández Luque, Jorge Luis (2023)
Intestinal amyloidosis is a rare and underdiagnosed systemic disease, which is characterized by the extracellular deposition of proteins that are grouped into amyloid fibers. This entity is rare and is usually a form of presentation in the context of systemic amyloidosis, the diagnosis of which is based on the presence of amyloid in histology. The clinic is usually non-specific; chronic diarrhea, weight loss, abdominal pain and bloating; Gastrointestinal bleeding is a very rare manifestation. The case of a 61-year-old woman with symptoms of weight loss, abdominal distension, nausea, vomiting and long hair is presented. Tomographically, a wall thickening of jejunal loops with contrast uptake was evidenced, a finding that was corroborated by a double-balloon anterograde stereoscopy in which multiple were evidenced. The pathology shows distorted and ulcerated villous architecture with positive histochemistry for Congo Red and LAMBDA (+++) immunohistochemistry. In addition, bone marrow aspirate and bone biopsy compatible with infiltration of Lambda chain monoclonal multiple myeloma were performed. During the hospital stay, the patient developed complications such as chronic malnutrition, recurrent infection and several episodes of intestinal subocclusion; characterized by intestinal pneumatosis; due to multiple episodes of these complications, the patient died. Within clinical practice in gastroenterology, intestinal amyloidosis as part of the differential diagnosis of upper gastrointestinal bleeding is infrequent, so a history of diagnosis of multiple myeloma or other monoclonal gammopathy associated with light chains is crucial for early diagnosis and adequate treatment.